Management of giant complex multiloculated ovarian cyst in a young female through minimal invasive laparoscopic surgery-a case study - Kunnaiah, Anitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Giant ovarian cysts are tumors characterized by diameters exceeding 10 cm. In recent times, these cysts have become exceedingly rare, attributed to their early diagnosis and management, facilitated by advancements in imaging technology. A 24-year-old woman presented in the Gynecology Department with the complaints like abdominal distention with mild pain and unexplained weight gain. Her medical history included a previous laparoscopic cystectomy, on the right side. An ultrasound examination disclosed a significant abdominopelvic multiloculated cystic lesion. Blood tests showed that the levels of markers CA-125, CA 19-9, alpha fetoprotein, LDH and HCG were within normal ranges, indicating no signs of malignancy. This benign giant complex multiloculated cyst has been effectively managed by means of 4 port laparoscopic technique. In premenopausal women, the occurrence of ovarian cysts is notably prevalent, with the majority being benign and functional. These cysts can attain significant sizes. Ultrasound imaging may also lead to misdiagnosis, necessitating the employment of advanced imaging modalities like MRI. Persistent complex ovarian cysts measuring more than 10 cm in diameter, especially if they present with symptoms, warrant consideration for surgical intervention. The presence of progressive abdominal distension in younger women should prompt a heightened suspicion of an ovarian tumor, specifically one of the benign varieties, such as a mucinous cystadenoma. In spite of being non-cancerous, their significant size can lead to complications, potentially rendering their surgical excision a life-threatening procedure.